PERAN FILOSOFI DAN IDENTITAS BUDAYA PADA RUMAH PANGGUNG WALEWANGKO MINAHASA - Tiagas, Doly Herling; Mohammad Imran (Universitas Bina Taruna Gorontalo, 2025)
The Walewangko Stilt House is a form of Minahasan vernacular architecture that is rich in philosophical values, spatial symbolism, and the cultural identity of its people. General studies on the material and construction aspects of Walewangko have been carried out extensively, but in-depth studies on the symbolic meaning, the relationship between spatial form and cultural identity, and strategies are still needed. This study aims to analyze the role of philosophy and cultural identity in the Walewangko Stilt House through a literature study approach. The results of the study show that the Walewangko House not only functions as a residence, but also as a symbol of social status, harmony with nature, and a binding force for the values of mutual cooperation in the Minah community. The preservation of Walewangko needs to be directed towards a revitalization strategy based on community participation to remain relevant amidst the challenges of modernization.